Sistem Informasi Pembayaran Mahasiswa di STMIK Antar Bangsa Tangerang - Febriani (LPPM STMIK ANTAR BANGSA, 2019)
Abstract— Student pay is a problem in an educational institution especially in college, student payment required by university to improve education quality and performance. Still manualization of the payment system will greatly impact on improving the quality and performance of education. Making a student payment application will be very helpful in the process of educational services, especially payment systems. It is expected that in the implementation of computerized payment system can help the parties involved in the system. Faster calculations, better service, and less time-consuming reporting. So that reporting can be used as a guide in decision making. Making payment applications, this aims to simplify and speed up the work that will be useful in making more efficient decisions. On the side of students making this payment application will facilitate the payment system that runs manually, so there will be no errors in the payment system, and can provide information that is very useful for campus residents.